NOMINEE AGREEMENTS IN THE PERSPECTIVE OF ECONOMIC CRIMINAL LAW: RISK IDENTIFICATION, PROOF, AND ENFORCEMENT - Wahyu Danang Setiadi; Lusia Sulastri (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
Nominee agreements (agreements on behalf of others) are often used as a tool to get around the prohibition of land ownership by Foreign Nationals (WNA) on Certificates of Title (SHM) in Indonesia. This article examines the position and characteristics of nominee agreements in the Indonesian legal system and assesses their potential as a means of economic crimes, especially related to corporate crimes, asset embezzlement, money laundering, and violations of agrarian provisions. With a qualitative data-based juridical-normative approach, this study identifies the legal risks that arise, the possibility of criminal liability for the parties involved (actual owners, nominees, intermediaries, and corporations), as well as obstacles and evidentiary strategies in criminal cases involving the covert agreement. The results of the study show that although the nominee agreement is originally a civil agreement, there is sufficient room for the application of economic delinquency when the agreement is used as a means of concealing ownership, facilitating the transfer of profits, or obscuring aspects of ownership in order to avoid legal prohibitions. Enforcement recommendations include strengthening evidentiary standards, inter-institutional coordination (prosecutor's office, police, BPN, PPAT), the use of financial forensic tools, and regulatory updates to clarify the criminal consequences of nominee practices that are detrimental to the public interest